Pemerolehan Bahasa Kedua Tataran Morfologis dan Sintaksis pada Anak Usia 5 Tahun (Kajian Psikolinguistik) - Rahmawati, Elviannur; Sesa, Yelniati; Wahyuni, Ian (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
Language acquisition by children begins when the child is 0 years old. When the child has successfully passed the acquisition of the first language, the child will move on to the next stage, namely the acquisition of the second language. Second language acquisition usually begins when a child is 5 years old. This research will examine the acquisition of a second language in a child named Freya who is 5 years old. The aim of this research is to see how Freya acquires a second language which focuses on the morphological level and the syntactic level. The method used in this research is a qualitative descriptive approach. The data collection technique used is by using the observation technique. Meanwhile, the data analysis technique used in this research is the matching method. The results of this research show that at the age of 5 years Freya is going through a period of acquiring a second language. If we look at the data in the form of words and also the results of discussions at the morphological and syntactic levels, Freya is able to use words with affixes and produce sentences but there are still errors in pronunciation and use of affixes.